Uncovering climate (in)justice with an adaptive capacity assessment: A multiple case study in rural coastal North Carolina. (May 2020) - Jurjonas, Matthew; Seekamp, Erin; Rivers, Louie; Cutts, Bethany
Highlights: Underserved rural coastal communities of color face a unique adaptation context. Engagement with underserved communities reduces perceived adaptive capacity. Perceived climate injustices pose barriers to coastal hazard adaptation, revealing instances of adaptation oppression. Improved outreach strategies are needed to overcome color blindness within climate science communication. Abstract: Climate change resilience is an area of praxis where efforts to enhance community adaptive capacity are informed by theory. However, there is growing evidence that ethnocentrism and privilege are shaping coastal management policies while many communities with climate justice issues struggle to build resilience. Particularly, rural coastal communities, contrasting urban areas, have limited access to centralized planning efforts, unique local contexts for outreach, compounding social vulnerabilities (job loss, out-migration, limited social services), and receive less attention from resilience researchers. Following calls to integrate climate justice into resilience praxis, we assess perceptions of adaptive capacity within predominately African American communities in a rural low-lying coastal region in eastern North Carolina. We add a climate justice lens to evaluate the previously-validated Rural Coastal Community Resilience (RCCR) framework. The RCCR is intended to improve planning efforts by providing climate change information, initiating conversations, and contributing to resilience theory. In contrast to its previous applications, engagement led to declines in perceived adaptive capacity. This result highlights that the information sharing goals of the engagement efforts were poorly aligned with community concerns and threat perceptions. Additionally, perceived climate injustices emerged revealing instances of adaptation oppression. This study recommends strategies to rethink traditional extension efforts to improve inclusiveness by deeply interrogating the inherent whiteness of standard modes of communicating climate science.